Association between sunlight exposure and risk of age-related macular degeneration: a meta-analysis - Hongjie Zhou (BMC Ophthalmology, 2018)
Abstract Background A substantial number of epidemiological studies have investigated the possible associations between sunlight exposure and Age-related Macular Degeneration (AMD), but the results from studies are inconsistent. The aim of this meta-analysis was to evaluate the association between sunlight exposure and the risk of AMD. Methods Relevant studies were searched using databases including PubMed, EMBASE, and Web of Science database. Two authors independently extracted data and assessed study quality. The random-effects model was used to calculate the pooled covariates-adjusted odds ratio (OR). Subgroup analyses based on study design, stage of AMD, method of exposure assessment, and study latitude were carried out. The heterogeneity across the studies was tested, as was publication bias. Results Fourteen eligible studies including 43,934 individuals based on the inclusion criteria were analyzed. The pooled OR for sunlight exposure and AMD was 1.10 (95% CI = 0.98–1.23). In addition, similar insignificant results were observed in further subgroup analyses based on stage of AMD, method of exposure assessment, and study latitude. Sun-avoidance behavior did not decrease the risk of AMD (OR = 1.12, 95% CI = 0.76–1.67). Moderate heterogeneity was observed in most of analyses. Conclusion The results indicate that sunlight exposure may not be associated with increased risk of AMD based on current published data.